Analisis Peran Foreign Direct Investment, Economic Complexity Index, dan Nilai Tambah Industri Manufaktur terhadap Pertumbuhan Ekonomi di 5 Negara ASEAN - Suparta, I Wayan; Renaldi, I Made (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Although ASEAN is known as a region with dynamic economic growth, significant disparities remain between countries in creating sustainable added value. Some countries, like Singapore, have successfully achieved economic transformation toward developed nation status, while others remain stuck in the middle-income category. This phenomenon raises questions about the role of external factors such as foreign direct investment (FDI) and structural factors like economic complexity (Economic Complexity Index/ECI) and industrial value added (Manufacturing Value Added/MVA) in driving economic growth in the ASEAN region. This study aims to analyze the influence of Foreign Direct Investment (FDI), Economic Complexity Index (ECI), and Industrial Value Added (MVA) on Gross Domestic Product (GDP) in five ASEAN countries, namely Indonesia, Malaysia, Thailand, the Philippines, and Singapore during the period 2017–2023. This study uses panel data obtained from the World Bank and Growth Lab. Data analysis was performed using EViews 9 software using a panel data regression approach. Model testing included the Chow and Hausman tests to determine the best model, and the results indicated that the Common Effects Model (CEM) was the most appropriate model for use in this study. The results show that FDI and MVA have a positive effect on Gross Domestic Product (GDP), indicating that increased foreign direct investment and a strengthening of the manufacturing sector play a significant role in driving national economic growth in the ASEAN region. Conversely, the ECI variable shows a negative effect on GDP, reflecting that increasing economic complexity has not yet fully yielded positive impacts due to imbalances between industrial structure, human resource capacity, and domestic innovation capabilities. This finding underscores the importance of a balance between strengthening economic complexity, the industrial sector, and improving the quality of human resources in accelerating economic growth in the ASEAN region.